2013
DOI: 10.4236/jasmi.2013.31004
|View full text |Cite
|
Sign up to set email alerts
|

Exhaled Breath Condensates as a Source for Biomarkers for Characterization of Inflammatory Lung Diseases

Abstract: Inflammatory lung diseases such as asthma and chronic obstructive pulmonary disease are common and difficult to diagnose and characterize. This is due in large part to difficulty in obtaining samples directly from the inflamed lung. The collection of lung secretions by traditional methods including bronchoalveolar lavage and induced sputum collection are limited by their invasive nature. Exhaled breath condensate (EBC) is a simple and non-invasive technique of collecting fluid samples, which are representative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…However, today there are commercial sampling devices that have been tested for this reason and provide reliable results. Each of them has its technical characteristics and parameters to be set before or during the collection process such as time 18 . Its analysis, on the other hand, seems to be not an easy task.…”
Section: Exhaled Breath Condensatementioning
confidence: 99%
“…However, today there are commercial sampling devices that have been tested for this reason and provide reliable results. Each of them has its technical characteristics and parameters to be set before or during the collection process such as time 18 . Its analysis, on the other hand, seems to be not an easy task.…”
Section: Exhaled Breath Condensatementioning
confidence: 99%
“…108 Analysis of exosomal markers (CD9, CD63 and CD81) demonstrated that there are controversial results about the presence of exosomes in EBC. 88,90 However, the results of the several separate studies demonstrated a successful detection of micro RNAs in EBC by quantitative real-time PCR which can provide new clinical insights into the non-invasive screening, early diagnosis and treatment of lung disease. [87][88][89][90]…”
Section: Micrornasmentioning
confidence: 99%
“…The detection of gastric pepsin in exhaled breath condensate (EBC) is a potential method of screening for reflux microaspiration. EBC involves condensation of water vapor from breath, which encompasses aerosolized particles of respiratory fluid, that may contain particles useful in the detection of the disease (11,12). EBC is gaining popularity as a research tool due to being inexpensive, non-invasive and safe (11).…”
Section: Introductionmentioning
confidence: 99%